Finite Element Analysis and optimization of a three-storey Parking Garage. Issue 1 (October 2020) - Kesheng, Zuo; Bin, Gu; Shunan, Hu; Jiefu, Wang; Jin, Wang
Abstract: Finite element analysis is one crucial means to evaluate and optimize the stability and safety of a three-storey parking garage. The geometric model of a three-storey parking garage was built with CATIA. A finite element model was set up by HyperMesh for static strength analysis in Abaqus. It is essential to consider some key factors such as simplification of mesh model, boundary conditions, weight and loads. The strength of the parking garage under full-load was analyzed. Finally, the frame structure of the parking garage was improved based on the result of simulation.